Peningkatan Kualitas Produk GRC (Glassfibre Reinforced Cement) Roster pada UD. XYZ Malang Menggunakan Metode Taguchi - Prabowo, Muhammad Sigit; Ekawati, Yurida (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2019)
The growth of manufacturing industries has caused the competition among companies becomes tighter. Therefore, companies need to make an effort to survive. One of the things that must be considered is the quality of products produced by the company. This research is conducted to design a refinement or quality improvement for GRC roster products in UD. XYZ Malang. The quality improvement is done with Taguchi method experimental design in order to get optimal combination for the materials. As for the orthogonal array notation used is L9(34) with gypsum (A), sand (B), cement (C), and water (D) as the controlling factors. The data processing is carried out using ANOVA towards the average value and SNR with larger the better classification. The ANOVA calculation is done in order to find out the significantly influential factors in product durability. The test done to find out the product durability is a pressure test. According to the result of data processing, the ratio of optimal mixture composition gypsum:sand: cement: wateris 2:2:2:1 (A3, B2, C3, dan D2). A confirmation experiment is conducted to the optimal composition. The analysis of the material cost for each experiment is done to justify the effectiveness of the optimal designed product chosen. Based on the pressure durability and cost calculation, the mean of result is 13,256 kg/cm2 for the pressure durability which indicates the quality is better than the exsisting product and able to save costs of Rp 1.630,927 in order to produce one GRC Roster.